Degradation of hexabromocyclododecane (HBCD) by nanoscale zero-valent aluminum (nZVAl). (April 2020) - Jiang, Yuting; Yang, Shiying; Liu, Junqin; Ren, Tengfei; Zhang, Yixuan; Sun, Xinrong
Abstract: Hexabromocyclododecane (HBCD) has been listed in Annex A of the Stockholm Convention on Persistent Organic Pollutants (POPs) in 2013, but till now there is a lack of efficient methods for its degradation. In this study, nanoscale zero-valent aluminum (nZVAl), an excellent reductant with a very low redox potential of E 0 (Al 3+ /Al 0 ) = −1.662 V and strong electron transfer ability, was used to reductively degrade HBCD. Nearly 100% HBCD was degraded within 8 h reaction at 25 °C in ethanol/water (v/v, 50/50) solution without pH adjustment. And about 67% cyclododecatriene (CDT) was obtained, which is the complete debromination product. What's more, the yield of Br − could achieve nearly 100% after optimizing conditions. The reaction was strongly promoted by increasing the dosages of nZVAl or decreasing the initial concentration of HBCD. The temperature had the most significant influence and the degradation was completed in 40 min with elevating the reaction temperature to 45 °C. The reaction mechanism was further revealed through the characterization of nZVAl particles before and after the reaction by SEM-EDS, TEM, HRTEM, XRD, and XPS. It was found that, after corrosion of the oxide film on the surface of nZVAl, metallic aluminum inside was exposed. The reactive sites were provided and electrons released were transferred from nZVAl to HBCD, causing HBCD degraded to dibromocyclododecadiene (DBCD) and then CDT by reductive debromination. These findings imply that nZVAl can degrade HBCD efficiently with no extra energy input and this offers a new idea for better treatment of HBCD. Graphical abstract: Image 1 Highlights: HBCD degradation by nZVAl is one of the highest efficiency methods. Nearly 100% debromination can be obtained under optimized conditions. HBCD was degraded to DBCD and then CDT through reductive debromination. The oxide film on the surface of nZVAl was corroded during the reduction reaction.